PENGARUH DOSIS PUPUK ORGANIK KOTORAN SAPI DAN MACAM PUPUK NPK TERHADAP PERTUMBUHAN DAN HASIL BAWANG MERAH ASAL BIJI (True Shallot Seed): Bawang merah, pupuk organik kotoran sapi, pupuk NPK - Fajar Arif Mustofa; Priyono, Priyono; Triyono, Kharis (FAKULTAS PERTANIAN UNIVERSITAS SLAMET RIYADI, 2023)
This study attempts to know the right combination of organic fertilizers best dose cow faeces and different kinds of npk fertilizer to the and the onion.A random group complete ( rakl ) factorials with two components used in this research.The first the cow faeces organic fertilizers ( p ) consisting of 3 the level 1 kg, 1,75 kg, and 2,5 kg / tenement.The second factor is the fertilizer npk ( m ) there are 4 the standard m0 ( without fertilizer ) npk, m1 ( npk pearls 16-16-16 60gr / ) swath, m2 ( npk phonska 20gr / ) swath, m3 ( npk mixed ( urea 28,5gr / tenement, sp-36 13,8gr / tenement, kcl 18gr / ) swath, there are 36 of an experiment after obtained remedial 12 combination treatment by 3.The quantity of a crop as many as 900 plants because every unit is 25 plants per plot and 3 plant used as sample observation. Based on research, organic fertilizers cow faeces and different kinds of npk not had have real impact on higher plants, number of leaves, or wide tubers, but had have real impact on fresh weight per plant and heavy fertilizer brangkasan kering.pemberian oragnik cow faeces ( 1,75 kg / tenement ) npk ( urea fertilizer and mixed 28,5gr / tenement, sp-36 13,8gr / tenement, kcl 18gr / tenement ) impact the onion on the number of bulbs per plant ( 21.00 ) tubers, the number of bulbs per tenement ( 306.00 ) tubers, heavy fresh bulbs per plant ( 199,22 ) gr, heavy brangkasan 14,92 gr ) ( dry.The use of a combination of organic fertilizers faeces npk cows and get the best result.